Developing Virtuous Learners: Uncovering the Profile of Pancasila Students in Primary Education for Character Development: Pembinaan Peserta Didik Berbudi Luhur: Mengungkap Profil Siswa Pancasila di Pendidikan Dasar untuk Pengembangan Karakter - Silvia, Rina; Amalia, Alfin Khoiro; Nabila, Lady Lailatun; Prapanca, Detak (International Consortium of Education and Culture Research Studies, 2023)
The aim of service is to develop character education, such as cultivating good character or noble character in students through an approach based on Pancasila values and improving the quality of character education at the basic education level by incorporating Pancasila values into the curriculum and school activities. The service method used is to create learning materials and modules that integrate Pancasila values into daily activities and the school curriculum. In addition, service is carried out to measure and record students' profiles of Pancasila, including their level of understanding of and application of these values in their daily lives. The results of this service show that students develop positive character, which is demonstrated by changes in behavior that reflect the values of Pancasila. The quality of character education increases at the basic education level because Pancasila values are incorporated into daily activities and the school curriculum. One of the results of this service is to provide a character education approach model based on Pancasila values that can be used by other schools. This approach will help develop overall character and shape students with strong characters, making them virtuous people who are responsible for their actions. Highlights: Integrated Curriculum Approach: Incorporating Pancasila values into daily activities and the school curriculum to foster character development among students at the basic education level. Measurable Impact: Implementing a method to measure and record students' profiles of Pancasila, including their understanding and application of these values, to assess the effectiveness of character education initiatives. Model for Character Education: Providing a character education approach model based on Pancasila values, offering a framework that can be adopted by other schools to cultivate virtues and responsibility in students through a holistic character development process. Keywords: Character Building, Elementary School, Pancasila